Pogovori in pogajanja avstrijskih ter nemških nacionalsocialistov s koroškimi Slovenci in dr. Julijem Felaherjem v letih 1933/1934 - Grafenauer, Danijel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
The following article treats conversations and negotiations of Austrian and German National socialists with Carinthian Slovenes and with Dr. Julij Felaherin 1933 and 1934. It was writtenon basis of yet impublished archival documents, newspaper articles and literature. It represents the part of Slovene national defence organisations and individuals in conversations and negotations with Nazis. These conversations became known because of inconspiracy and especially the Austrian press took advantage of it. The article presents activities of the Austrian consulate in Ljubljana, which reported yhe situation in Slovenia and Yugoslavia to Vienna regularly. It also proves the surmise that Felaher was allowed (by Yugoslav/Slovene authorities) to negotiatewith Nazis, but it remains unknown, how far Felaher'sconnections with Slovene and Yugoslav authorities extended, and also after what and whose instructions he took part in negotiations. The conversations and negotiations failed. It is also clear that Felaher's participation in these conversations and negotiations with Nazis was nothing but pure patriotism of Carinthian Slovene. In supposed willingness of Nazis to resign the plebiscite area in Carinthia he saw an opportunity to correct the unjust border in Carinthia. Unfortunately, there are almost no preserved documents about such conversations. The conversations between Slovene representatives and nationa socialists continued also even after 1034,but there is no prove about their success.
Keywords: Felaher, Julij; Nacisti; Pogajanja; 1933-1934; Carinthian Slovenes; Koroški Slovenci; Emigranti; Jugoslavija; Yugoslavia; Austria; Avstrija; history; zgodovina; Koroška